Hubungan Stres Akademik Dan Intensitas Penggunaan Media Sosial Instagram Dengan Kualitas Tidur - Siti Rahayu rahayu; Octa Reni Setiawati; Elsy Junilia (Program Studi Psikologi Islam, 2025)
Abstract Academic stress and excessive social media use are crucial issues for adolescents, suspected of affecting sleep patterns and quality, which impacts physical and mental health. This study aims to examine the relationship between academic stress, intensity of Instagram use, and sleep quality in adolescents. The study subjects involved 161 students of SMAN 7 and SMAN 16 Bandar Lampung, aged 15–18 years, actively attending school, and using social media. The sample was taken using a quota sampling technique from grades 10, 11, and 12. The instruments used were the PSQI Scale for sleep quality, the SL-SI for academic stress, and the Instagram Use Intensity Scale adapted from the FIS. Multiple regression analysis using SPSS showed a significant relationship between academic stress and intensity of Instagram use with sleep quality (R² = 10.4%, p = 0.034 and 0.001). The majority of subjects had high sleep quality (56.5%), moderate academic stress (57.1%), and moderate intensity of Instagram use (87.5%). These findings indicate both partial and simultaneous influences of independent variables on sleep quality. Keywords: Sleep quality, academic stress, intensity, social media, Instagram